Effectiveness of Experimental Laboratory Methods on Understanding the Concept of Light, Science Processes Skills, And Scientific Attitudes of Students - Adrianus Nasar; Melkyanus Bili Umbu Kaleka (Universitas Muhammadiyah Makassar, 2019)
Light is the material in science teaching and learning that uses a lot of laboratory activities and equipment. Learning is more effective if done through cooperative small groups. This study determines the effectiveness of science learning uses laboratory experimental methods for understanding concepts, science process skills, and scientific attitudes of students in SMP Negeri 2 Ende. This study used a non-randomized quasi-experimental design through the pretest-posttest control group. The sample amounted to 72 people consisting of 37 people in the experimental group and 35 in the control group. The research instrument used questions about understanding concepts, observation sheets, and scientific attitude questionnaires. Data obtained in the form of normalized gain and analyzed using Compare Mean - Independent Sample T Test. The results of the study showed that the laboratory experimental method was effective in improving understanding of concepts, science process skills, and scientific attitudes of students. The findings of this study, science learning is recommended to use laboratory experiment methods in which students communicate very intensively with each other and their teachers, use tools and materials, and influence students' scientific attitudes.Keywords: Laboratory Experimental Methods, Understanding Concepts, Science Process Skills, And Scientific AttitudesMateri cahaya adalah materi dalam sains yang menggunakan kegiatan dan peralatan laboratorium. Belajar lebih efektif jika dilakukan melalui kelompok kecil yang kooperatif. Penelitian ini bertujuan menentukan efektivitas pembelajaran sains menggunakan metode eksperimen laboratorium untuk memahami konsep, keterampilan proses sains, dan sikap ilmiah siswa di SMP Negeri 2 Ende. Penelitian ini menggunakan desain Nonrandomized Control Group, Pretest–Posttest Design. Sampel berjumlah 72 orang yang terdiri dari 37 orang pada kelompok eksperimen dan 35 pada kelompok kontrol. Instrumen penelitian menggunakan pertanyaan tentang tes untuk pemahaman konsep, lembar observasi untuk keterampilan sains, dan angket untuk sikap ilmiah. Data diperoleh dalam bentuk gain ternormalisasi dan data dianalisis menggunakan perbandingan rerata gain (Compare Mean – Independent Sampel T Test). Hasil penelitian menunjukkan bahwa metode eksperimen laboratorium efektif dalam meningkatkan pemahaman konsep, keterampilan proses sains, dan sikap ilmiah siswa. Temuan penelitian ini yaitu pembelajaran sains direkomendasikan untuk menggunakan metode percobaan laboratorium di mana siswa berkomunikasi sangat intensif satu sama lain dan guru mereka, menggunakan alat dan bahan, dan mempengaruhi sikap ilmiah siswa.Kata kunci: Metode Eksperimen, Pemahaman Konsep, Keterampilan Proses Dan Sikap Ilmiah Peserta Didik